The Role of Patriarchal Culture in Hindering Women’s Participation in the Political Arena Especially in a Muslim- Majority Democracy - ali su’udin, Achmad Faried irfany; Ahmad Nabil Nashiri (Journal of Political Islam, 2025)
ABSTRACT Women’s participation in politics is a crucial aspect of achieving an inclusive and equitable democracy. However, the strong presence of patriarchal culture in Indonesian society remains one of the main factors hindering women’s involvement in the political sphere, including in Muslim-majority societies, whose socio-religious values often reinforce patriarchal norms in political and social life. This study aims to analyze how patriarchal culture limits women’s access to politics and to identify strategies that can enhance their representation. Using a literature review method, this research refers to various sources discussing the relationship between patriarchal culture and the low level of women’s political participation. The findings indicate that male dominance in political structures, gender stereotypes, limited access to political education, and minimal social support are the primary barriers preventing women from actively engaging in politics. To address these issues, strategic measures such as improving women’s political education, implementing affirmative policies like a 30% women’s representation quota, and providing organizational support through training and networking are necessary. With a comprehensive and sustainable approach, women’s political participation can be strengthened to create a more representative and gender-responsive governance system.